10p+9-11-p=-4p-8-6p

Simple and best practice solution for 10p+9-11-p=-4p-8-6p equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 10p+9-11-p=-4p-8-6p equation:


Simplifying
10p + 9 + -11 + -1p = -4p + -8 + -6p

Reorder the terms:
9 + -11 + 10p + -1p = -4p + -8 + -6p

Combine like terms: 9 + -11 = -2
-2 + 10p + -1p = -4p + -8 + -6p

Combine like terms: 10p + -1p = 9p
-2 + 9p = -4p + -8 + -6p

Reorder the terms:
-2 + 9p = -8 + -4p + -6p

Combine like terms: -4p + -6p = -10p
-2 + 9p = -8 + -10p

Solving
-2 + 9p = -8 + -10p

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '10p' to each side of the equation.
-2 + 9p + 10p = -8 + -10p + 10p

Combine like terms: 9p + 10p = 19p
-2 + 19p = -8 + -10p + 10p

Combine like terms: -10p + 10p = 0
-2 + 19p = -8 + 0
-2 + 19p = -8

Add '2' to each side of the equation.
-2 + 2 + 19p = -8 + 2

Combine like terms: -2 + 2 = 0
0 + 19p = -8 + 2
19p = -8 + 2

Combine like terms: -8 + 2 = -6
19p = -6

Divide each side by '19'.
p = -0.3157894737

Simplifying
p = -0.3157894737

See similar equations:

| 95=25+10*x | | ln(6x+6)=ln(5x+2) | | 3sinx/8 | | 2x+23=3x | | -8+30+-9= | | 11+n=27 | | 6*x-2*x=520 | | x-2*6*x=520 | | sin(x)+5x=0 | | x=5log(x) | | x-2*y=520 | | x*x-9x=-18 | | x-5log(x)=0 | | 9=-3(2b+7) | | 2x^2w^5*8x*2w^4= | | 6x+30=2x+10 | | 2x^2+3x-4=8x-4 | | 3ab*2cd=4ac | | 5(3a-2)=50 | | 2x*2x=4x | | (M+3)x^2+2m(x+1)+3=0 | | sqrt(4x+8)+7=4x | | 16-2(x-1)=x | | 4x-6x-6=3+14 | | 8x+24=6x+40 | | -1/4=1/5b | | 11(x-8)-8=28x-232 | | -1/4=1/5 | | 5x+9=1x+17 | | ln(x)+10x=4 | | 3x/7+4/5=6/7 | | 5(4x+9)= |

Equations solver categories